PENGUKURAN KINERJA BANK SYARIAH INDONESIA PRE-MERGER DAN PASCA MERGER MELALUI METODE MAQASHID SYARIAH INDEX (MSI) DAN SHARIA CONFORMITY PROFITABILITY (SCnP) - Rahma, Maulida Fauzia; Darwanto, Darwanto (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2024)
This research aims to analyze the performance of Bank Syariah Indonesia (BSI) for the period 2018 to 2023 using the Maqashid Syariah Index (MSI), profitability, and Sharia Conformity And Profitability (SCnP) methods. The object of the study is BSI pre-merger (2018-2020) consisting of Bank BNI Syariah (BNIS), Bank BRI Syariah (BRIS), and Bank Syariah Mandiri (BSM), as well as Bank Syariah Indonesia (BSI) post-merger (2021-2023). Secondary data from the annual financial reports of BNIS for the period 2018-2020, BRIS for the period 2018-2020, BSM for the period 2018-2020, and BSI for the period 2021-2023. The analysis method used in this study uses The Simple Additive Weighting (TSAW), Comparative Performance Index (CPI), and Quadrant Analysis Measurement (QAM) approaches. The results indicate the highest MSI value was in 2023 and the lowest in 2020. The highest profitability value was in 2019 and the lowest in 2022. The results of the study using the SCnP method showed that those in the Upper Right Quadrant (URQ) had high sharia conformity and profitability values in 2019 and those in the Lower Left Quadrant (LLQ) had low sharia conformity and profitability values, namely in 2021 and 2022, so that on average the performance after the merger was better than pre-merger.